Nurse-led home visitation programme to improve health-related quality of life and reduce disability among potentially frail community-dwelling older people in general practice: A theory-based process evaluation - Stijnen M.M.N. (BioMed Central Ltd., 2020)
10.1186/s12875-014-0173-x